Need of the hour: pharmacovigilance study of SGLT-2 inhibitors - Pradhan, Sapna; A., Tejus; Koley, Mrinalini; Mathur, A. G. (International Journal of Research in Medical Sciences, 2019)
Background: Diabetes mellitus represents a global pandemic. Various pharmacotherapy and non-pharmacotherapy measures are advocated for its control. The latest in the pharmacotherapy are Sodium Glucose Transporter -2 (SGLT-2) inhibitors, widely used. Many studies suggest adverse effects related to SGLT-2 inhibitors, evidence still not conclusive and few data from India. Hence this study was planned. Methods: Cross-sectional study over a period of 02 months, recorded demographic details and history of various adverse drug reactions reported with the use of SGLT-2 inhibitors. Results: Majority of the study participants were females (58%) and belonged to the age group of 40-70 yrs. Urinary tract infections (UTI) and genital infections was more seen in the users of dapagliflozin, followed by empagliflozin and canagliflozin. Conclusions: SGLT-2 Inhibitors offer a unique therapeutic approach to the management of Diabetes Mellitus. Further evaluation of the safety profile and the risk-benefit analysis is the need of the hour.